A Correlational Study About Students’ Grammar Mastery And Their Skill In Rewriting Short Narrative Text After Watching Movies At Bung Hatta University English Department - Adzanil Prima Septy; Dewinta Zuhari (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research was to determine the relationship between students' proficiency in simple past tense grammar and their ability to write a short narrative movie at Bung Hatta University's English Department. This study employed a correlational research design, with 30 participants from a pool of 37 students. Two tests were used to collect data, namely grammar and writing tests.This study discovered a positive correlation between grammar mastery and writing skills indicating that students who excel at grammar also have better writing skills in this study. This research suggested that English lecturers should motivate their students to watch more short films to improve their writing and grammar skills. On the other hand, students should engage in more grammar exercises in order to improve their writing skills, especially when writing narrative texts. To sum up, this research's findings underscore the significance of grammar mastery in developing writing abilities, particularly in narrative writing, and the value of incorporating visual aids like movies (i.e. short YouTube films) into language instruction to encourage students to enhance their writing and grammar skills.